Directed Evolution of Methanomethylophilus alvus Pyrrolysyl-tRNA Synthetase Generates a Hyperactive and Highly Selective Variant - Fischer, Jonathan T.; Söll, Dieter; Tharp, Jeffery M. (Frontiers in Molecular Biosciences, 2022)
Pyrrolysyl-tRNA synthetase (PylRS) is frequently used for site-specific incorporation of noncanonical amino acids (ncAAs) into proteins. Recently, the active site of Methanomethylophilus alvus PylRS (MaPylRS) has been rationally engineered to expand its substrate compatibility, enabling the incorporation of difficult ncAAs. However, mutations beyond the active site that enhance the enzymatic properties of MaPylRS have not been reported. We utilized phage-assisted noncontinuous evolution (PANCE) to evolve MaPylRS to efficiently incorporate Nε-Boc-L-lysine (BocK). Directed evolution yielded several mutations outside of the active site that greatly improve the activity of the enzyme. We combined the most effective mutations to generate a new PylRS variant (PylRSopt) that is highly active and selective towards several lysine and phenylalanine derivatives. The mutations in PylRSopt can be used to enhance previously engineered PylRS constructs such as MaPylRSN166S, and PylRSopt is compatible in applications requiring dual ncAA incorporation and substantially improves the yield of these target proteins.